Pengelolaan Risiko Kecurangan pada Inspektorat Daerah Istimewa Yogyakarta dengan Pendekatan ERM - Rizma Drajad Siti Apriyanti; Annisa Rahima (Value : Jurnal Manajemen dan Akuntansi, 2026)
Risk of fraud is a major obstacle in realizing accountable and transparent governance, especially for internal supervisory institutions. Therefore, effective fraud risk management is crucial to suppres the potential fraud in order to achieve organizational goals. The purpose of this research is to analyze the implementation of fraud risk management, assess the alignment of its implementation with Enterprise Risk Management (ERM) indicators, and map the factors that influence it in the Inspectorate of The Special Region of Yogyakarta (DIY) environment. By adopting a mixed-methods approach with a descriptive design, this study collected quantitative data through questionnaires distributed to all DIY Inspectorate employees totaling 54 respondents. Meanwhile, qualitative data was collected through in-dept interviews and documentation studies. The data analysis process was done by using descriptive statistical techniques and thematic analysis. The research findings show that fraud risk management in the agency has integrated five main elements of ERM. Those are the control environment, risk assessment, control activities, information and communication and monitoring. In general, ERM implementation is considered effective in promoting corruption and fraud prevention, transparency and institutional accountability. However, several obstacle remain, such as limited human resoureces, suboptimal risk assessment instruments and internal communication quality. On the other hand, a leaders commitment, a strong culture of integrity and the availability of public complaints system are the main factors for the success of the risk management.